2022
DOI: 10.1039/d1qo01873f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of diverse C–S/C–Se bonds via nickel catalyzed reductive coupling employing thiosulfonates and a selenosulfonate under mild conditions

Abstract: A nickel-catalyzed reductive cross coupling between organic iodides and thiosulfonates and a selennofonate under mild conditions is disclosed. This pracitical method provides facile access to a series of unsymmetrical thioethers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…On the basis of the above results and previous studies, ,, a plausible reaction mechanism was proposed (Scheme ). First, the active Pd(0) species was produced in situ from Pd­(hfac) 2 and XantPhos; then, oxidative addition with thiosulfonates 1 resulted in the formation of intermediate A .…”
mentioning
confidence: 56%
“…On the basis of the above results and previous studies, ,, a plausible reaction mechanism was proposed (Scheme ). First, the active Pd(0) species was produced in situ from Pd­(hfac) 2 and XantPhos; then, oxidative addition with thiosulfonates 1 resulted in the formation of intermediate A .…”
mentioning
confidence: 56%
“…A considerable number of methods to insert a phenylseleno group into (hetero)arenes or alkenes have been developed. 15–19 One of the most classic and common strategies is using various transition metals such as Pd, 20,21 Rh, 22–25 Cu, 26–28 Ni 29,30 etc. as catalysts (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Another synthetic route to forge the C-Se bond is through metal catalyzed cross-coupling reactions of aryl halides, which always require high temperature or complex selenium sources. 29 Over the past ten years, a series of metal-free strategies involving the synthesis of aryl selenoethers have been developed. For example, Braga et al 31 and Bolm et al 32 reported the selenation and the thiolation of 1,3,4-oxadiazoles by adding low-cost bases.…”
Section: Introductionmentioning
confidence: 99%
“…The heteroaryl thiosulfonates we prepared successfully solved this problem, providing a feasible solution for the preparation of unsymmetric heteroaryl thioethers with complex structures. We employed nickel-catalyzed reductive thiolation of halides with thiosulfonates to obtain a wide range of unsymmetric alkyl−aryl 28 or aryl−aryl 29 sulfides. First, we investigated the substrate scope of iodides.…”
mentioning
confidence: 99%